Respuesta :

Answer:

  6^6

Step-by-step explanation:

The applicable rule of exponents is ...

  (a^b)/(a^c) = a^(b-c)

In this problem, that means ...

  (6^9)/(6^3) = 6^(9-3) = 6^6

__

It can help to remember that an exponent signifies repeated multiplication. Written out without exponents, the problem is ...

  [tex]\dfrac{6\cdot6\cdot6\cdot6\cdot6\cdot6\cdot6\cdot6\cdot6}{6\cdot6\cdot6}=6\cdot6\cdot6\cdot6\cdot6\cdot6=6^6[/tex]

Note that the 3 instances of 6 in the denominator cancel 3 from the numerator. Clearly, the effect is the same as subtracting exponents.

Answer: 6^6

Step-by-step explanation: Formula - (a^b)/(a^c) = a^(b-c)

keeping the formula in mind;

= 6^9/6^3= 6^(9-3)

= 6^6